Model Pembelajaran Kooperatif Tipe Think-Pair-Share (TPS): Karakteristik, Keunggulan, dan Implementasinya - Ryan Irfan Nuruddin; Maolidatul Imamah; Agung Setyawan (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
This research aims to describe the meaning, characteristics, advantages and implementation of the think-pair-share (TPS) type cooperative learning model. This research uses a qualitative approach that focuses on literature studies. The distribution of coding references on common themes such as characteristics and implementation is relatively uniform, indicating consensus between sources. In contrast, technical themes such as implementation steps and the cooperative notion of TPS vary, enriching the analysis with different perspectives. Table data supports the effectiveness of the TPS model in improving student learning outcomes, motivation, communication, and cooperation, with experimental classes performing better than controls. The overall findings corroborate the relevance of TPS as an effective and collaborative learning method at various levels and subjects.